Fe2O3 Porous Film with Single Grain Layer for Photoelectrochemical Water Oxidation: Reducing of Grain Boundary Effect. Issue 1 (29th October 2015) - Jia, Lichao; Bogdanoff, Peter; Ramírez, Alejandra; Bloeck, Ulrike; Stellmach, Diana; Fiechter, Sebastian
Abstract : In this study, a promising alternative method for addressing grain boundary issues in hematite (α‐Fe2 O3 )‐based photoanodes is presented. The porous α‐Fe2 O3 films are prepared by dip coating a polymerizable precursor onto fluorine‐doped tin oxide (FTO) substrates. The photoelectrochemical (PEC) performance of α‐Fe2 O3 photoanodes is characterized and optimized through controlling the annealing temperature and the number of deposition cycles. Samples of improved crystallinity consisting of a layer of hematite particles of 50 nm in diameter exhibit highest photoresponses of 1.04 mA cm −2 at 1.23 V versus a reversible hydrogen electrode (RHE), and 2.0 mA cm −2 before the dark current onset at 1.7 VRHE . This study indicates that the PEC performance of hematite can be enhanced greatly by an improved crystallinity, particle texture, and a better control of grain boundary effects. Abstract : Thin film α ‐Fe2 O3 photoanodes are fabricated with a facile synthesis technique with the aim to enhance their oxygen generation behavior by limiting the number of grain boundaries. An optimized porous α‐Fe2 O3 photoanode achieves a photocurrent density of 1.04 mA cm −2 at 1.23 V and 2.0 mA cm −2 at 1.7 V versus a reversible hydrogen electrode using a W‐I lamp of 40 mW cm −2 .